2016
DOI: 10.1016/j.jcrc.2015.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation after lung transplantation

Abstract: IntroductionTo explore the hypothesis that early ventilation strategies influence clinical outcomes in lung transplantation, we have examined our routine ventilation practices in terms of tidal volumes (Vt) and inflation pressures.Methods 124 bilateral lung transplants between 2010 and 2013 were retrospectively assigned to low (<6ml/kg), medium (6-8ml/kg) and high (>8ml/kg) Vt groups based on ventilation characteristics during the first 6 hours after surgery. Those same 124 patients were also stratified to low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…The timing and number of tidal volume values recorded varied significantly between the studies. The most detailed continuous dataset reported the mean tidal volume over the first 6 h post‐transplant based on hourly measures of tidal volume 15 . This study reported no significant difference in intensive care unit (ICU) length of stay or 6‐month survival between three tidal volume sub‐groups (<6/6–8/>8 mL/kg rPBW).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The timing and number of tidal volume values recorded varied significantly between the studies. The most detailed continuous dataset reported the mean tidal volume over the first 6 h post‐transplant based on hourly measures of tidal volume 15 . This study reported no significant difference in intensive care unit (ICU) length of stay or 6‐month survival between three tidal volume sub‐groups (<6/6–8/>8 mL/kg rPBW).…”
Section: Resultsmentioning
confidence: 94%
“…There were 3/11 studies that reported the association between tidal volume and PGD grade within the first 72 h 9,10,15 . Two of the studies identified no significant association 9,15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been challenging to determine the optimal PEEP for mechanical ventilation of lung transplant recipients (Diamond and Ahya, 2014). A previous study showed that the low, medium and high tidal volumes had similar effects on short-and medium-term prognoses in lung transplantation recipients (Thakuria et al, 2016). Although a high PEEP level is associated with a high risk of pneumothorax and bronchial anastomotic complications, it is also associated with increased bronchial blood flow.…”
Section: Personalized Ventilationmentioning
confidence: 99%
“…While most lung transplant centers report using low tidal volume ventilation strategies during and after lung transplant surgery, extension of studies of mechanical ventilator management into the early post-operative period may also impact development of PGD. One retrospective single center study in the United Kingdom reported that only approximately half of lung transplant recipients received tidal volumes < 8mL/kg in the first 6 hours after transplant surgery [14]. Use of a specific ventilator management protocol may improve the frequency of low tidal volume ventilation in this peri-operative population.…”
Section: Modifiable Clinical Risk Factorsmentioning
confidence: 99%